Control Module Quality Reliability Test In Data Acquisition In Simulation - Wandy Nata Adiguna; Adi Sastra P Tarigan; Solly Aryza (Sean Institute, 2021)
This paper describes the main advantages of this DAS module which is that it can be manufactured at a very affordable price and provides good performance is commonly used in industrial control systems. Alternative data acquisition system (DAS) modules can use the LabVIEW interface in motor control systems. The DAS module is controlled by the ATmega64 AVR microcontroller which will communicate in both directions with LabVIEW using the serial communication method. Which is used to obtain 8-bit digital input, 8-bit digital output, 8 analog input channels, and also 2 analog output channels. Digital inputs can be used for 0-5V and 0-24V voltages. The digital output is made open collector with a